Robust cobalt catalyst for nitrile/alkyne [2+2+2] cycloaddition: synthesis of polyarylpyridines and their mechanochemical cyclodehydrogenation to nitrogen-containing polyaromatics* - Wang, Chang-Sheng (2022)
The transition-metal-catalyzed [2+2+2] cycloaddition of nitriles and alkynes is an established synthetic approach to pyridines; however, these cycloadditions often rely on the use of tethered diynes or cyanoalkynes as one of the reactants. Thus, examples of efficient, fully intermolecular catalytic [2+2+2] pyridine synthesis, especially those employing unactivated nitriles and internal alkynes leading to pentasubstituted pyridines, remain scarce. Herein, we report on simple and inexpensive catalytic systems based on cobalt(II) iodide, 1,3-bis(diphenylphosphino)propane, and Zn that promote [2+2+2] cycloaddition of various nitriles and diarylacetylenes for the synthesis of a broad range of polyarylated pyridines. DFT studies support a reaction pathway involving oxidative coupling of two alkynes, insertion of the nitrile into a cobaltacyclopentadiene, and C-N reductive elimination. The resulting tetra- and pentaarylpyridines serve as precursors to hitherto unprecedented nitrogen-containing polycyclic aromatic hydrocarbons via mechanochemically assisted multifold reductive cyclodehydrogenation.